1973
DOI: 10.1084/jem.138.6.1413
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of Energy Metabolism in the Cultivated Macrophage

Abstract: The in vitro differentiation of the monocyte into the larger, structurally more complex, functionally more active macrophage is accompanied by an increase in glycolytic activity as well as an increased dependence on aerobic metabolism (1-3). There is little information regarding the factors that regulate these changing patterns of energy metabolism during differentiation. In view of previous observations that environmental constituents have a profound effect on endocytosis (4, 5), one of the principal function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
3
12
0
Order By: Relevance
“…Similar observations were made in endothelial cells, which are tolerant to hypoxia and which reduce HSP70 to levels observed under low oxygen tension [27]. Endothelial cells as well as macrophages are, in contrast to most other mammalian cell types, well adapted to low oxygen levels by changing their metabolism to anaerobiosis glycolysis [8,19,32]. Thus, we may assume that these cells are not stressed by this condition, which may be the reason why they do not stimulate HSP70 in response to hypoxia.…”
Section: Discussionsupporting
confidence: 59%
“…Similar observations were made in endothelial cells, which are tolerant to hypoxia and which reduce HSP70 to levels observed under low oxygen tension [27]. Endothelial cells as well as macrophages are, in contrast to most other mammalian cell types, well adapted to low oxygen levels by changing their metabolism to anaerobiosis glycolysis [8,19,32]. Thus, we may assume that these cells are not stressed by this condition, which may be the reason why they do not stimulate HSP70 in response to hypoxia.…”
Section: Discussionsupporting
confidence: 59%
“…This increase in PyKi and PFK, under hypoxic conditions, may in turn be related to another more general mechanism. We have shown that changes in energy metabolism enzyme activities (both glycolytic and those of oxidative phosphorylation) are regulated by 02 tension in alveolar and peritoneal macrophages (13,31). The present studies demonstrate the operation of this adaptive mechanism in another cell type.…”
Section: Discussionmentioning
confidence: 55%
“…3C); also, we found that the Akt inhibitor Akt VIII (10 M) did not inhibit the hypoxia-stimulated BMM survival in the absence of CSF-1 over a 48-h period (data not shown). The downregulation by hypoxia of the antiapoptotic Bcl-2 and Bcl-x L proteins, in both CSF-1-depleted and cycling BMM, is perhaps surprising given the literature on other cells (21) but could be due to suppression of overall protein synthesis reported during hypoxia for macrophages (50) and other cell types (51); consistent with this possibility, we found that mRNA levels of the two antiapoptotic proteins did not parallel the loss of protein (data not shown). In any case, Bcl-2 and Bcl-x L expression did not correlate with enhanced macrophage survival for CSF-1-depleted BMM; also, cycling BMM, that is, in the presence of a high CSF-1 concentration, whose survival is not modulated by hypoxia, also showed the same reduction.…”
Section: Discussionmentioning
confidence: 85%